Circular RNAs and Hepatocellular Carcinoma: New Epigenetic Players With Diagnostic and Prognostic Roles - Aishanjiang, Kedeerya; Wei, Xin-dong; Fu, Yi; Lin, Xinjie; Ma, Yujie; Le, Jiamei; Han, Qiuqin; Wang, Xuan; Kong, Xiaoni; Gu, Jinyang; Wu, Hailong (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related death worldwide. Due to the lack of potent diagnosis and prognosis biomarkers and effective therapeutic targets, the overall prognosis for survival is poor in HCC patients. Circular RNAs (circRNAs) are a class of novel endogenous non-coding RNAs with covalently closed loop structures and implicated in diverse physiological processes and pathological diseases. Recent studies have demonstrated the involvement of circRNAs in HCC diagnosis, prognosis, development and drug resistance, suggesting that circRNAs may be a class of novel targets for improving HCC diagnosis, prognosis and treatments. In fact, some artificial circRNAs have been engineered and showed their therapeutic potential in treating of HCV infection and gastric cancer. In this review, we introduce the potential of circRNAs as biomarkers for HCC diagnosis and prognosis, as therapeutic targets for HCC treatments and discuss the challenges in circRNA research and chances of circRNA application.